ChemInform Abstract: Copper‐Catalyzed Aerobic Oxidative Amination of Arylboronic Acid with Aminal under Base‐Free Conditions. Issue 36 (15th August 2013) - Zhou, Yanping; Xie, Yinjun; Yang, Lei; Xie, Pan; Huang, Hanmin
Abstract Amination is carried out in the presence of air with symmetrical aminals to give the products in moderate yields.